On Transformation Involving Basic Analogue of Multivariable H-Function - Dinesh Kumar; Frédéric Ayant; Jessada Tariboon (Journal of Function Spaces)
In this article, fractional order q-integrals and q-derivatives involving a basic analogue of multivariable H-function have been obtained. We give an application concerning the basic analogue of multivariable H-function and q-extension of the Leibniz rule for the fractional q-derivative for a product of two basic functions. We also give the corollary concerning basic analogue of multivariable Meijer’s G-function as a particular case of the main result.